Implementation of Signature based Intrusion Detection System with Snort Rule on E-Voting System - Muhammad Adnan Khairi A.S.; Eddy Prasetyo Nugroho; Rizky Rachman J. (Universitas Pendidikan Indonesia, 2023)
Security is an important thing for everyone, including network security, which everyone needs, including the security at web server, there are problems encountered on the server one of which is on the E-voting site server, this server serves to store all the data storage of votes in an election between registered candidates. In this paper we propose a solution to detect these attacks using SNORT IDS. snort will detect an attack by adding a special rule to handle the attack. We tested the proposed solution by comparing the system against four different attacks, the result was that DDoS attacks had the greatest number of data packets compared to other attacks.